The Effects of Indefinite Nonlinear Boundary Conditions on the Structure of the Positive Solutions Set of a Logistic Equation - Ramos-Quoirin, H (Academic Press, 2014)
We investigate a semilinear elliptic equation with a logistic nonlinearity and an indefinite nonlinear boundary condition, both depending on a parameter ?. Overall, we analyze the effect of the indefinite nonlinear boundary condition on the structure of the positive solutions set. Based on variational and bifurcation techniques, our main results establish the existence of three nontrivial non-negative solutions for some values of ?, as well as their asymptotic behavior. These results suggest that the positive solutions set contains an S-shaped component in some case, as well as a combination of a C-shaped and an S-shaped components in another case. © 2014 Elsevier Inc.